الحكومة الرقمية ودورها في ترشيد النفقات العمومية في الدول العربية خلال الفترة (2003-2020) - بوعتلي, محمد (جامعة الوادي - University of Eloued, 2023)
This study aimed to analyze and measure the role of E-Government in rationalizing public expenditures in Arab countries (17 countries) during the period (2003-2020). To achieve this goal, the method of sectional time series data (panel models) was relied on and on the R program . The study found a significant negative effect of E-Governmen development on the rate of public expenditures in Arab countries. Specifically, if the e-government development index increases by 10%, the rate of public expenditures in Arab countries will decrease by 0.30%, indicating that the development of E-Governmen in Arab countries has a positive impact on rationalizing public expenditures
The E-Government and its role in rationalizing public expenditures in the Arab countries during the period (2003-2020)
مقال
Keywords: الحكومة الرقمية ; النفقات العمومية ; الدول العربية ; نماذج البانل; E-Government; public expenses; Arab Countries; Panel Models.